Dual ARB/NEP Inhibition with LCZ696 improved endothelial regeneration in an experimental model of metabolic syndrome - García, Rodrigo Damián (2019)
To demonstrate that LZC696 (L) reduces organ damage in an experimental model of metabolic syndrome, were explored two mechanisms: anti-inflammatory effects through the IL-6Ralpha pathway and through MAS1R, the production of endothelial repair mediated by VEGFR2+/CD133+ endothelial progenitor cells (EPCs). Experimental model of metabolic syndrome was realized by WKY rats and SHRs. SHR and WKY received a fructose diet in drinking water at 10% v/v for 12 weeks (FFHR and FFR receptivity). Chronic treatment with L: (68 mg / kg per day for 6 weeks) and valsartan (V) (34 mg / kg per day for 6 weeks, as control equimolar group. Was determined: SBP, fast glycaemia and TTGO, left ventricular hypertrophy (HVI), vascular remodelling, hsCPR expression, and vascular expression in mesenteric tissue of IL-6Ralfa, STAT3, VEGFR2 and CD133 were determined. The experimental model was confirmed. L treatment reverted SBP, HVI, remodelling and vascular inflammation, decreased STAT3 expression and hsCPR in FFHR. Additionally, the most important finding was that L produced an increase in the expression of resident EPCs in the endothelial tissue of mesenteric tissue.